Sharon Pollock First Woman of Canadian Theatre - Coates, Donna (The West, 2015)
As playwright, actor, director, teacher, mentor, theatre administrator, and critic, Sharon Pollock has played an integral role in the shaping of Canada's national theatre tradition, and she continues to produce new works and to contribute to Canadian theatre as passionately as she has done over the past fifty years. Pollock is nationally and internationally respected for her work and support of the theatre community. She has also played a major role in informing Canadians about the "dark side" of their history and current events. This collection, comprised entirely of new and original assessments of her work and contribution to theatre, is both timely and long overdue. Includes a new play titled "Sharon's Tongue" by the Playing with Pollock Collective With contributions by: Kathy K. Y. Chung Donna Coates Carmen Derksen Sherrill Grace Martin Morrow Jeton Neziraj Wes Pearce Tanya Schaap Shelley Scott Jerry Wasserman Jason Weins Cynthia Zimmerman